71st issue Info Kampus UiTM Sarawak Bulletin January 2016 - Wee, Roselind; Lau, Ung Hua; Metom, Lilly; Abg Bohari, Dayang Faridah; Johari, Aiza; Abang, Mohamad; Ch'ng, Looi Chin; Yeo Jiin Yih, Jacinta (Universiti Teknologi MARA, Sarawak, 2016)
UiTM Transformation Programme or Trans4U has great implications for UiTM Sarawak. This programme is set to restore UiTM's sustainability and bring about higher levels of academic excellence which is what UiTM Sarawak is continuously striving for. With the tagline "Menjuruterai Destini, Menjuarai Legasi" ("Engineering Destiny, Advocating Legacy"), UiTM aims to empower superiority and ensures sustainability. UiTM Sarawak has always striven for continuous improvement. "Menjuruterai Destini" (Engineering Destiny) reflects the aim of UiTM to become a world renowned research-intensive entrepreneurial university. UiTM Sarawak staff, particularly the academic staff, have always been encouraged to take part in research in various fields. Many have won recognition and awards at national and international levels. With the implementation of this transformation programme, UiTM Sarawak staff and students will be even more motivated to strive for the highest level of achievements.